Characterization and use of the spent beam for serial operation of LCLS. (10th April 2015) - Boutet, Sébastien; Foucar, Lutz; Barends, Thomas R. M.; Botha, Sabine; Doak, R. Bruce; Koglin, Jason E.; Messerschmidt, Marc; Nass, Karol; Schlichting, Ilme; Seibert, M. Marvin; Shoeman, Robert L.; Williams, Garth J.
<x xml:space="preserve">Abstract</x> X‐ray free‐electron laser sources such as the Linac Coherent Light Source offer very exciting possibilities for unique research. However, beam time at such facilities is very limited and in high demand. This has led to significant efforts towards beam multiplexing of various forms. One such effort involves re‐using the so‐called spent beam that passes through the hole in an area detector after a weak interaction with a primary sample. This beam can be refocused into a secondary interaction region and used for a second, independent experiment operating in series. The beam profile of this refocused beam was characterized for a particular experimental geometry at the Coherent X‐ray Imaging instrument at LCLS. A demonstration of this multiplexing capability was performed with two simultaneous serial femtosecond crystallography experiments, both yielding interpretable data of sufficient quality to produce electron density maps.